Mariangela Tempera and Keir Elam (eds.), Twelfth Night, dal testo alla scena (Altre Modernità, 2017)
Mariangela Tempera and Keir Elam (eds.), Twelfth Night, dal testo alla scena(Bologna, Emil, 2017, 285 pp. ISBN 978-88-6680-226-6)by Giuliana Iannaccaro